Study on wear behaviour characteristics of ZrO2 and ZrN coated AZ91D Mg alloy - Allasi , Haiter Lenin; Kumaradhas, Poomani; Sivapragash, Murugesan; Vettivel, S.C. (Journal of Mining and Metallurgy, Section B: Metallurgy, 2023)
The as-received AZ91D Mg alloy was coated with ZrO2 and ZrN ceramics using the Physical Vapour Deposition (PVD) process. Dry sliding wear investigations were performed in a pin-on-disc wear tester at a sliding velocity of 2-8 m/s and a normal load of 2-10 N. The wear mechanisms such as abrasion, delamination, thermal softening, and oxidation were observed. The results showed that PVD coating increased the wear resistance of AZ91D Mg alloy. The worn surface was examined with Scanning Electron Microscope (SEM).